Phytochemical Analysis, Antispasmodic, Myorelaxant, and Antioxidant Effect of Dysphania ambrosioides (L.) Mosyakin and Clemants Flower Hydroethanolic Extracts and Its Chloroform and Ethyl Acetate Fractions - Fahd Kandsi; Raffaele Conte; Mohamed Marghich; Fatima Zahra Lafdil; Mohamed F. Alajmi; Mohamed Bouhrim; Hamza Mechchate; Christophe Hano; Mohammed Aziz; Nadia Gseyra (Molecules, 2021)
Dysphania ambrosioides (L.) Mosyakin and Clemants is an annual or ephemeral perennial herb used traditionally in the Mediterranean region in folk medicine to treat various illnesses, including those related to the digestive system. This study aims to assess the antispasmodic, myorelaxant, and antioxidant effects of D. ambrosioides flower hydroethanolic extract and its chloroform and ethyl acetate fractions in a comparative study to evaluate the result of the extraction type on the potential activity of the extract. Both rat and rabbit jejunum were used to evaluate the antispasmodic and myorelaxant effect, while the antioxidant effect was evaluated using DPPH, a ferric reducing power assay, and a beta-carotene bleaching test. LC/MS-MS analysis was carried out to reveal the composition of the different types of extract. Following the results, the hydroethanolic extract showed a significant myorelaxant effect (IC50 = 0.39 ± 0.01 mg/mL). Moreover, it was shown that the hydroethanolic extract demonstrated the best antispasmodic activity (IC50 = 0.51 ± 0.05 mg/mL), followed by the ethyl acetate (IC50 = 4.05 ± 0.32 mg/mL) and chloroform (IC50 = 4.34 ± 0.45 mg/mL) fractions. The antioxidant tests showed that the hydroethanolic extract demonstrated high antioxidant activity, followed by the ethyl acetate and chloroform fractions. The LC/MS-MS analysis indicates that the plant extract was rich in flavonoids, to which the extract activity has been attributed. This study supports the traditional use of this plant to treat digestive problems, especially those with spasms.